A DFT bottom-up approach on non-fullerene acceptors: what makes highly efficient acceptors - Freitas, Arthur V. [UNESP] (2024)
Over the last two decades, the demand for efficient and sustainable ways of producing electricity increased, motivating the development of high-efficient photovoltaic devices. In this context, bulk heterojunction organic solar cells based on non-fullerene acceptor (NFA) molecules have shown promising performances due to their versatility of synthesis, processing advantages, good stability to sunlight exposition, and high efficiencies (up to 18%). In particular, the high chemical versatility of these materials allows the synthesis of a number of distinct NFAs with varied performances, so that theoretical studies are essential to guide the prospection of new optimized compounds. In the present study, density functional theory-based (DFT) calculations were conducted to investigate the electronic structure of well-known building blocks of NFA, to assess how the fusion of these units influences the optoelectronic properties of the NFAs cores. The results allow us to identify relevant patterns for the design of optimized systems and define dominant sites for charge transfer processes, offering novel insights into the interpretation of operational mechanisms.